2007
DOI: 10.3390/12020188
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Photochemistry of 1-Iodocyclohexene:Influence of Ultrasound on Ionic vs. Radical Behaviour

Abstract: Simultaneous application of UV light and ultrasonic irradiation to a reaction mixture containing 1-iodocyclohexene is reported. The irradiation of 1-iodocyclohexene in methanol was carried out with or without addition of zinc. The effect of ultrasound or mechanical stirring on this solid-liquid system was also compared. The irradiation of 1-iodocyclohexene in methanol in the presence of zinc increases the yield of the nucleophilic trapping product, compared with the yield after irradiation in the absence of zi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Since the first report on the use of ultrasound to promoting reaction rates [ 1 ], the wide applications of sonochemistry in synthesis have attracted a lot of attention, in not only academia, but also in various fields of chemistry, materials science and chemical engineering [ 2 , 3 , 4 ]. Ultrasound is a kind of sound lying between 20 kHz and 10 MHz which cannot be heard by the human ear, and it has been reported that high-intensity ultrasound could exceed the attractive force of molecules to produce high concentrations of H· and OH· radicals in water [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since the first report on the use of ultrasound to promoting reaction rates [ 1 ], the wide applications of sonochemistry in synthesis have attracted a lot of attention, in not only academia, but also in various fields of chemistry, materials science and chemical engineering [ 2 , 3 , 4 ]. Ultrasound is a kind of sound lying between 20 kHz and 10 MHz which cannot be heard by the human ear, and it has been reported that high-intensity ultrasound could exceed the attractive force of molecules to produce high concentrations of H· and OH· radicals in water [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…This compound was prepared in analogy to a published protocol. [ 15 ] A solution of cyclohexanone 1 (500 mg, 3.24 mmol) in MeOH (2 ml) was added with stirring at °C to H 2 NNH 2 ·H 2 O (~85%, 1.7 ml, 1.67 g, 44.3 mmol) in a Pyrex tube. A colorless precipitate developed and the mixture was stirred for 1 h at 60°C and cooled to rt.…”
Section: Methodsmentioning
confidence: 99%
“…Oxime 4 [ 14 ] and an analogous hydrazone were synthesized with standard protocols starting with commercially available 4‐ tert ‐butylcyclohexanone ( 1 ). Reaction of 1 with hydrazine hydrate did not furnish the expected simple cyclohexylidenehydrazone but a 1,2‐dicyclohexylidenehydrazine 5 , [ 15 ] which we considered similarly suitable for the intended investigations (Scheme 1).…”
Section: Synthesis Of Cyclohexane‐derived Compoundsmentioning
confidence: 99%
“…In recent years, ultrasound-assisted organic synthesis (UAOS) utilizing environmentally benign reagents and conditions has been one of the most fascinating developments in the arena of modern synthetic chemistry owing to its green credentials [ 1 , 2 , 3 , 4 , 5 ]. The notable features of the aqueous UAOS come from its advantages such as easier manipulation, energy conservation, rate enhancement and insolubility of the final products which facilitates their isolation by simple filtration [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%